2009
DOI: 10.1111/j.1440-1746.2009.06030.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal: Gastric mucosa‐associated lymphoma presented with unique vascular features on magnified endoscopy combined with narrow‐band imaging

Abstract: Gastrointestinal: Gastric mucosa-associated lymphoma presented with unique vascular features on magnified endoscopy combined with narrow-band imagingGastric lymphoma arising from mucosal associated lymphoid tissue (MALT) has distinct clinical and histological characteristics compared with nodal B-cell lymphoma. Magnified endoscopy (ME) combined with narrow band imaging (NBI) is widely used and the usefulness is well recognized for the diagnosis of gastritis and gastric cancer. However, there has been no report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…In a recent report that reviewed 14 patients with esophageal MALT lymphoma, the endoscopic findings of 11 patients showed submucosal tumor-like lesions; nine of these had craniocaudal extension (22). The present case showed both of these endoscopic findings, and we additionally observed the presence of abnormal blood vessels similar to a tree-like appearance, which is a typical characteristic of gastric lesions in MALT lymphoma (39, 40). This characteristic was recently reported in an esophageal lesion by Kudo et al (25).…”
Section: Discussionsupporting
confidence: 79%
“…In a recent report that reviewed 14 patients with esophageal MALT lymphoma, the endoscopic findings of 11 patients showed submucosal tumor-like lesions; nine of these had craniocaudal extension (22). The present case showed both of these endoscopic findings, and we additionally observed the presence of abnormal blood vessels similar to a tree-like appearance, which is a typical characteristic of gastric lesions in MALT lymphoma (39, 40). This characteristic was recently reported in an esophageal lesion by Kudo et al (25).…”
Section: Discussionsupporting
confidence: 79%
“…In addition, H. suis -associated gastric MALT lymphoma was recently documented to have a nodular gastritis-like appearance, which is distinct from the common type [ 63 ]. The endoscopic findings on narrow band imaging (NBI) magnifying endoscopy were also characterized by a tree-like appearance (TLA), which corresponded to abnormally large vessels resembling a tree trunk with long, bare branches [ 64 ]. Moreover, endocytoscopy may be useful for detecting intra-glandular aggregation of cellular components and small to moderately sized nuclei in gastric MALT lymphoma, but further studies are needed [ 65 ].…”
Section: Endoscopic Findingsmentioning
confidence: 99%
“…In 2009, we reported a case of gastric mucosa-associated lymphoid tissue (MALT) lymphoma presenting with unique vascular features [12]. In the report, we defined the tree-like appearance (TLA) on the images of abnormal blood vessels which resembled branches from the trunk of a tree in the shiny mucosa, in which the glandular structure was lost (Figure 3).…”
Section: Narrow Band Imagingmentioning
confidence: 99%
“…There are few organized reports on the endoscopic findings of gastric MALT lymphoma [6]- [8], with only a few case reports published on its diverse endoscopic findings [9]- [11]. Recent studies have reported the useful-ness of NBI magnifying endoscopy in diagnosing gastric MALT lymphoma [12]- [15]. In addition, the usefulness of endoscopic ultrasound findings as a predictor of the therapeutic efficacy of H. pylori eradication has been reported [16] [17].…”
Section: Introductionmentioning
confidence: 99%